Romania, 1916-1941 : a political history - Deletant, Dennis, 1946- (London ; New York : Routledge Taylor & Francis Group, 2022)
"This study challenges the rose-tinted view of the interwar period in Romanian history, which is often judged against the darkness of almost five decades of Communist rule. Romania, 1916-1941 is a useful resource for upper-level undergraduates, postgraduates, and scholars interested in foreign policy, politics, society, internationalisation, and late development in interwar Central and Eastern Europe"--
Romania 1916-1929. Politics -- Romania 1918-1940. Economics and Society -- Foreign Policy. 1918-1940 -- The Cession of Bessarabia and Northern Bukovina -- Romania 1930-1940. Politics -- The National Legionary State, 1940-1941 -- Military Dictatorship -- Romania at War, 1941.